Goosebumps: The Horror at Camp Jellyjam - Stine, R L (Scholastic Ltd, 1995)
And why are they so obsessed with winning? It might have something to do with the hideous, slimy discovery lurking in the darkness....
Keywords: Horror & Ghost Stories; Juvenile Fiction